What Psychological Type Can Do in the Organization - Suman, Elena (European Journal of Economics and Business Studies, 2020)
Each one of us being either boss or subordinate approaches activities at the workplace from the perspective of the language of the Psychological type. Employees develop strategies, solve problems, reduce stress in the workplace through the perspective of the Psychological type, and the same psychological type helps us to address different situations we encounter in the workplace as effectively as possible. Once the psychological type is identified, the managers pay more attention to the employee’s work style so that he can use it in the most profitable way, as well as in developing effective relations with the employees within the organization. An employee who is ready to take risks, fulfill initiatives and become effectively productive, of course involves a lot of factors but surely one could see that, workplace performance is affected by skills, dominant and specific that a person holds. If the workplace tasks are compatible with the type of personality of the individual, then the work itself can become an interesting, stimulating one. Experts in the field of human resources say that the way in which we work today is also the effect of changing tomorrow; we must achieve more using less time, less people, and fewer resources.